Career Capital Development of Highly Skilled Self-Initiated Expatriates - Mello, Rodrigo; Suutari, Vesa (Palgrave Macmillan, 2023)
Existing literature and research on the career impacts of expatriation have focused on expatriates sent abroad by their employers. In turn, the career experiences of other types of global workers (e.g., migrants and self-initiate expatriates) are more limited in number. However, a growing number of individuals self-initiate their international professional journey and search for a job abroad without organizational support. Such experiences often offer similar developmental opportunities as expatriation within companies, but our evidence is still limited. Due to their developed international competencies, self-initiated expatriates (SIE) represent an attractive global staffing alternative for organizations assuming that they understand how expatriation develops individuals’ competencies. Based on an internet survey and interviews with SIE members of two Finnish trade associations, this chapter investigates the career capital (CC) development of highly skilled Finnish SIEs. The two associations identified individuals working abroad in 2015 and 2016, and they received our questionnaire in 2020. The present study’s results support the view that SIEs generally develop their CC fairly extensively when working abroad. This view contrasts with previous studies that emphasize more negative views on the development of SIEs, who are described as facing challenges in finding suitable jobs abroad that fit their level of education and CC. Therefore, the context in which the SIEs work may impact their learning opportunities and perception of the value of such international work experience.
Keywords: Self-initiated expatriates; Career capital; career development; fi=Henkilöstöjohtaminen|en=Human Resource Management|